The Combination of Hemogram Indexes to Predict Exacerbation in Stable Chronic Obstructive Pulmonary Disease - Liu, Xuanqi; Ge, Haiyan; Feng, Xiumin; Hang, Jingqing; Zhang, Fengying; Jin, Xiaoyan; Bao, Hong; Zhou, Min; Han, Fengfeng; Li, Shengqing; Qian, Yechang; Jie, Zhijun; et al. (Frontiers in Medicine, 2020)
Background: Chronic Obstructive Pulmonary Disease (COPD) is characterized by pulmonary and systemic inflammatory processes, and exacerbation of COPD represents a critical moment in the progression of COPD. Several biomarkers of inflammation have been proposed to predict acute exacerbation. However, their use is limited in routine clinical practice. The purpose of our study is to explore the prognostic efficacy of novel inflammatory hemogram indexes on the exacerbation among stable COPD patients. Method: A total of 275 stable COPD patients from Shanghai COPD Investigation Comorbidity Program were analyzed in our study. Blood examination, lung function test, CT scans and questionnaires were performed at baseline and routine follow-ups. Clinical characteristics (such as PLR, SII, SIRI and other hemogram indexes) and information of exacerbations were collected. Relationship between hemogram indexes and diverse degrees of exacerbation were assessed by Logistic regression. Receiver operating characteristic curve and area under curve were used to evaluated the ability of hemogram indexes to predict exacerbation of COPD. Furthermore, the discrimination and accuracy of combined indexes are measured by ROC and calibration curve. Result: There was a significant positive correlation between PLR levels and total exacerbation of COPD patients in stable stage in a year. And the predictive ability of PLR exceeded any other ratio indexes, with an AUC of 0.66. SII and SIRI placed second only to PLR, with AUC of 0.64 and 0.64- respectively. When combining PLR with other indexes (gender, COPD year and SGRQ scores), they were considered as the most suitable panel of index to predict total exacerbation. Based on the result of ROC curve and calibration curve, the combination shows optimal discrimination and accuracy to predict exacerbation event in COPD patients. Conclusion: The hemogram indexes PLR, SII and SIRI were associated with COPD exacerbation. Moreover, the prediction capacity of exacerbation was significantly elevated after combining inflammatory hemogram index PLR with other indexes, which may be a promisingly simple and effective marker to predict exacerbation in patients with stable COPD.